Effectiveness of Cannabis Oil as an Adjuvant Therapy in Patients with Severe Knee Osteoarthritis: A Randomized, Double-Blind Study - Prucksikanont, Warin; Nakeim, Prangrugee; Sitasut, Isanee; Thianman, Thuchirapan (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: The removal of cannabis from Thailand’s narcotic drug list presents both opportunities and challenges for medical use. The effectiveness of cannabis oil in treating severe knee osteoarthritis in patients awaiting total knee arthroplasty was evaluated in this study. Methods: Thirty-two patients with severe knee osteoarthritis, unresponsive to conservative treatment, were enrolled and divided into two equal groups. The control and experimental groups received syrup and cannabis oil, respectively, at night for 30 days. Pain and quality of life (QOL) were assessed using the Numeric Rating Scale (NRS), and the Knee Injury and Osteoarthritis Outcome Score (KOOS), respectively. Liver and kidney functions were also assessed. Results: The experimental group showed a significant reduction in NRS scores compared to the control group (p = 0.00015). Significant improvements were observed in KOOS subscales for pain, activities of daily living (ADL), and QOL (p = 0.01). However, the symptoms subscale improvement was not significant (p = 0.14). When comparing the KOOS subscales, no significant differences were observed between the groups (p > 0.05). Liver and kidney function remained stable in both groups. Despite these improvements, the changes did not reach a minimal clinically important difference (MCID), indicating limited clinical perceptibility to the patients. Conclusions: Cannabis oil was associated with significant improvements in pain, ADL, and QOL in severe knee osteoarthritis. Although improvements did not meet MCID thresholds, observed benefits suggest potential for pain management. Larger controlled studies are recommended to confirm its clinical efficacy in pain management.